2020
DOI: 10.1002/jmv.25797
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the first four SARS‐CoV‐2 cases in Chile

Abstract: The current pandemic caused by the new coronavirus is a worldwide public health concern. To aboard this emergency, and like never before, scientific groups around the world have been working in a fast and coordinated way to get the maximum of information about this virus when it has been almost 3 months since the first cases ORCID Andrés E. Castillo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 10 publications
(9 reference statements)
7
57
0
Order By: Relevance
“…In the last several months, residents in more than 180 countries/regions have been affected by SARS-CoV-2, and the emergence of mutations might already make important contributions to virus adaption to new environments and selective pressures, which in turn can impact transmissibility, pathogenesis and immunogenicity of SARS-CoV-2 [33]. It has been reported that variant SARS-CoV-2 genomes occurred in different areas [34][35][36][37][38]. Our results also showed that some mutations were widely distributed, and their occurrence rates had different dynamic fluctuations.…”
Section: Orf3a-s Complexes But Weaker Affinities In G251v Orf3a-m Anmentioning
confidence: 99%
“…In the last several months, residents in more than 180 countries/regions have been affected by SARS-CoV-2, and the emergence of mutations might already make important contributions to virus adaption to new environments and selective pressures, which in turn can impact transmissibility, pathogenesis and immunogenicity of SARS-CoV-2 [33]. It has been reported that variant SARS-CoV-2 genomes occurred in different areas [34][35][36][37][38]. Our results also showed that some mutations were widely distributed, and their occurrence rates had different dynamic fluctuations.…”
Section: Orf3a-s Complexes But Weaker Affinities In G251v Orf3a-m Anmentioning
confidence: 99%
“…We have already published the phylogenetic analysis of the first four genomes detected in Chile that revealed the two variants derived from strains present mainly in Europe (16).…”
Section: Introductionmentioning
confidence: 99%
“…The S type, which is evolutionarily older and less aggressive, might have increased in relative frequency due to relatively weaker selective pressure [32]. In a recent study from Chile on the first four cases of SARS-CoV-2/COVID-19 in Chile, authors suggest that at least two different viral variants entered into the country, from Europe and Asia [33].…”
mentioning
confidence: 99%